2020
DOI: 10.1111/1462-2920.14933
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of interdomain taxonomic patterns in urban street mats

Abstract: Summary Streets are constantly crossed by billions of vehicles and pedestrians. Their gutters, which convey stormwater and contribute to waste management, and are important for human health and well‐being, probably play a number of ecological roles. Street surfaces may also represent an important part of city surface areas. To better characterize the ecology of this yet poorly explored compartment, we used filtration and DNA metabarcoding to address microbial community composition and assembly across the city … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Subsequently, the 16S rRNA gene data were analyzed with mothur version 1.39.5 (Schloss et al, 2009), as described in Hervé and Lopez (2020). Briefly, the 16S rRNA gene reads were denoised by removing any reads having ambiguous bases, homopolymers longer than 8 bp, and having a length inferior to 280 bp or superior to 320 bp.…”
Section: Comparative Analysis Of the Gut Bacteriome Of Alates And Wor...mentioning
confidence: 99%
“…Subsequently, the 16S rRNA gene data were analyzed with mothur version 1.39.5 (Schloss et al, 2009), as described in Hervé and Lopez (2020). Briefly, the 16S rRNA gene reads were denoised by removing any reads having ambiguous bases, homopolymers longer than 8 bp, and having a length inferior to 280 bp or superior to 320 bp.…”
Section: Comparative Analysis Of the Gut Bacteriome Of Alates And Wor...mentioning
confidence: 99%
“…Due to the heavy pollution and harsh conditions, traffic areas and their runoff can be classified as an extreme environment. Early research looked mainly at microbial communities found in sediments of infiltration basins (17), on the effect of de-icing salts (18,19), the biofilm of road gutters (20), or on the denitrification potential of road runoff receiving biofilters (21). More comprehensive analysis on the microbiology of road runoff are missing and most of the microbes and their community functioning in this polluted environment remain unknown, despite we can assume that they will be of relevance for the receiving water bodies (groundwater and surface waters) (22,23).…”
Section: Introductionmentioning
confidence: 99%